Exploring the spillover effect of spirituality and workplace deviant behavior - Abdul Rahim, Abdul Rahman; Mohamed Thaheer, Ahmad Shazeer; Shabudin, Alwi; Abdul Wahab, Abdul Rahman; Hashim, Noor Azmi (Centre for Enhancing Knowledge (CEK), UK, 2014)
This current study, which is framed within the context of the spillover theory, examined workplace deviant behaviour, as response to individual daily spirituality experience.More specifically, this study examined the relationship between spirituality and workplace deviant behaviour.Data was collected from 165 adults, employed in a diverse set of occupations in three manufacturing companies producing similar product category.Their participation was on voluntary basis. Data analyses revealed two forms of workplace deviant behaviour (WDB), namely, Organizational WDB and Interpersonal WDB.Results of regression analyses demonstrated negative and significant relationship between spirituality, Organizational WDB and Interpersonal WDB.